Manajemen Pementasan Reguler Musik di Café Neon Surabaya oleh Grup Musik Januback dalam Perspektif Pendidikan Seni - abraham miracle (Jurnal Pendidikan Sendratasik, 2026)
This The Januback Music Group is the house band at Café Neon in Surabaya, having managed to maintain its presence amid the competition in the nightlife industry, despite focusing solely on the pop genre. The group’s uniqueness lies in its self-management system, which is run by its members who also serve as its administrators. This study aims to identify the elements and management strategies in their regular performances, while also examining their role from an arts education perspective. This study employs a descriptive qualitative approach based on the theory of Handayaningrum and Soeyono (2018). Data were collected through observation, interviews, and document analysis. The results indicate that performance management has been implemented in a structured manner through the 6M elements (men, money, methods, materials, machines, markets) and management functions encompassing planning, organizing, directing, and controlling. The strategies employed include intensive internal coordination, clear task allocation, regular rehearsals, and adapting performance concepts to the audience’s characteristics. From an arts education perspective, these regular performance activities serve not only as a form of entertainment but also as a learning medium that fosters discipline, creativity, cooperation, responsibility, and artistic skills among the members of the music group. These findings confirm that the success of a performance is determined not only by musical ability but also by systematic management.